Economic performance of the “Emping Melinjo” household industry and the entrepreneurial character of the business owner - Buddhi Satyarini Triwara (EDP Sciences, 2021)
Many of the melinjo chips household industries in Bantul have been operating for a very long time, are still included in the household industry scale, proving that the industry is not developing. This study aims to determine: 1) the entrepreneurial character of the melinjo chips household industry; 2) factors that correlate with entrepreneurial character 3) business feasibility of melinjo chips; 4) the relationship between entrepreneurial character and economic performance of the business. This research is a descriptive study conducted with a survey method of 60 respondents in Bantul Regency. The method analysis are using table analysis and regretion analysis The results showed that the entrepreneurial character of the emping melinjo business owner in Bantul being studied were achievement motivation and leadership (quite low), responsive and creative in facing the future (low) and business networks (very low). The character of achievement motivation influences other entrepreneurial characters. The external factor that affects the character of entrepreneurship is government support. The feasibility level of the melinjo chips business is measured by an RC ratio of 1, a capital productivity level of 3% and a labor productivity level of 206,800 / HOK. The entrepreneurial character of a broad business network and availability of labor have an effect on the feasibility of an R/C business and capital productivity. Internal factors of family support have a negative effect on company performance in labor productivity.